2019
DOI: 10.1038/s41598-019-55027-8
|View full text |Cite
|
Sign up to set email alerts
|

Defined factors to reactivate cell cycle activity in adult mouse cardiomyocytes

Abstract: Adult mammalian cardiomyocytes exit the cell cycle during the neonatal period, commensurate with the loss of regenerative capacity in adult mammalian hearts. We established conditions for long-term culture of adult mouse cardiomyocytes that are genetically labeled with fluorescence. This technique permits reliable analyses of proliferation of pre-existing cardiomyocytes without complications from cardiomyocyte marker expression loss due to dedifferentiation or significant contribution from cardiac progenitor c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…For example, AKT-mediated nuclear localization of the forkhead box transcription factor FoxM1 promotes cardiomyocyte proliferation in the developing heart [ 69 ], but FoxM1 expression decreases during the postnatal period [ 19 ] ( Figure 1 A). Likewise, the transcription factors E2f2 and E2f4 promote embryonic cardiomyocyte mitotic activity and are downregulated postnatally ( Figure 1 A); however, forced expression of E2f2/4 in adult cardiomyocytes leads to massive cell death [ 70 , 71 , 72 ]. Finally, Isl1 promotes embryonic cardiomyocyte proliferation by activating Fgfs and Bmps [ 73 ], which elicit a downstream proliferative response, and cooperate with Gata4 to express Hand2, another transcription factor that activates proliferative genes [ 74 , 75 ].…”
Section: Transcriptional Regulation Of Postnatal Cardiomyocyte Matmentioning
confidence: 99%
“…For example, AKT-mediated nuclear localization of the forkhead box transcription factor FoxM1 promotes cardiomyocyte proliferation in the developing heart [ 69 ], but FoxM1 expression decreases during the postnatal period [ 19 ] ( Figure 1 A). Likewise, the transcription factors E2f2 and E2f4 promote embryonic cardiomyocyte mitotic activity and are downregulated postnatally ( Figure 1 A); however, forced expression of E2f2/4 in adult cardiomyocytes leads to massive cell death [ 70 , 71 , 72 ]. Finally, Isl1 promotes embryonic cardiomyocyte proliferation by activating Fgfs and Bmps [ 73 ], which elicit a downstream proliferative response, and cooperate with Gata4 to express Hand2, another transcription factor that activates proliferative genes [ 74 , 75 ].…”
Section: Transcriptional Regulation Of Postnatal Cardiomyocyte Matmentioning
confidence: 99%
“…Similar to E2F1, E2F3 overexpression was also associated with cell death (215). Instead, contrasting data have been obtained for the apoptotic response induced by E2F2 and E2F4, with initial studies demonstrating a reduction in cell death upon E2F2 and E2F4 overexpression in cultured neonatal cardiomyocytes (215), and more recent studies describing an increase in apoptosis of cultured adult mammalian cardiomyocytes (217). Interestingly, co-expression of E2F2 and BEX1 [Brain Expressed X-Linked (Bex)] was demonstrated as a strategy to induce cardiomyocyte cell cycle activity, without cell death (217).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…Recent studies reported that binding of agrin to αDG could contribute to enhanced CM proliferation. To expedite such changes, modulating the stiffness of microenvironments could synergistically initiate CM proliferation via dedifferentiation–proliferation–redifferentiation of CMs (Yahalom-Ronen et al, 2015 ; Wang et al, 2017 ; Judd et al, 2019 ).…”
Section: Stimulation Signals For Cardiomyocyte Proliferationmentioning
confidence: 99%